Daisies for innocence - Cattrell, Bailey; Cattrell, Bailey (Cattrell, Bailey. Enchanted garden mystery, 2016)
"Ellie's life has blossomed in Poppyville, California, since she opened Scents & Nonsense, a custom-made-perfume store. Her skills with aromas and botanical essences--some from her very own garden--seem almost ... supernatural. Her perfumes can evoke emotions, bring about change, or simply make people happy. Customers are flocking to the store to buy her wares or just to sit in her beautiful garden, sip tea and enjoy homemade cookies. But she smells trouble when she learns that her part-time assistant Josie is dating her ex. And before she can tell the young woman to beware of his charms, she finds Josie dead in the Enchanted Garden. Now the prime suspect in Josie's murder, Ellie must search for the real culprit in Josie's past--because it'll take a miracle to nip this problem in the bud ..."--